The Plasmodium vivax Pv41 surface protein: Identification and characterization (2008)
Recently, Plasmodium vivax has been related to nearly 81% of malaria cases reported in Central America and the Mediterranean. Due to the difficulty of culturing this parasite species in vitro, most studies on P. vivax have focused on the identification of new antigens by homology comparison with P. falciparum vaccine candidate proteins. In this study, we have identified and characterized a Pf41 homologue in P. vivax, hence named Pv41, by following such approach and using web-available bioinformatics databases, molecular techniques and immunochemistry assays. Pv41 protein is a 384-amino-acid-long antigen encoded by a single exon that exhibits two s48/45 domains characteristic of gametocyte surface proteins. We have also demonstrated Pv41 transcription and expression during late intra-erythrocytic parasite stages and defined its subcellular localization on the parasite surface. © 2008 Elsevier Inc. All rights reserved.